Ethical Principles for Handling Laboratory Animals in an Experiment with Pathogenic Biological Agents of the I-II Groups - V. G. Germanchuk; A. P. Semakova; N. Yu. Shavina (Проблемы особо опасных инфекций, 2018)
Current international and major part of national documents, regulating experiments on laboratory animals, is set out in Bioethics Convention 3”R”. Presently this 3”R” principle is still relevant and commonly accepted global standard. Objective of the study was to verify the compliance of the staff at the institute with the ethical principles of biological safety when handling laboratory animals infected with pathogenic biological agents (PBA) of the I-II groups, performing diagnostic, experimental, and manufacturing activities. Results and discussion. Carried out analysis of ethical principle implementation, when working with biomodels infected with pathogenic biological agents of the I-II groups, performing scientific and manufacturing activities shows that operational procedures comply with the requirements of biological safety and regulations of ethical code, as well as international standards for humane treatment to animals in biomedical investigations. Conclusions. The work with laboratory animals infected with PBA of the I-II groups at the premises of RusRAPI “Microbe” meets the requirements of biological safety and norms of ethical code. Experiments on animals are aimed at obtainment of new scientific knowledge, preservation and improvement of human health, and also monitoring of natural foci of particularly dangerous infections following the rules of 3“R” bioethical concept.